Product development of banana rope woven baskets - Taravet, Vinai; Songneam, Sermsri; Phetdam, Nopparat; Rojsuvanichakorn, Wannapa (Journal of Home Economics Technology and Innovation, 2022)
Research study on product development of banana rope woven baskets have a purpose To study and develop new products from banana rope To survey satisfaction towards the development of banana rope basket products and to design banana rope products. a study on the use of banana peels in the design of banana rope basket product development. By the design process of all 3 types of banana rope woven baskets, the design factors are Take a survey about the product development model of banana rope woven baskets. that the respondents wanted the most Then used to produce containers for daily use and satisfaction surveys from 30 consumers. The results of the research found that after completing a survey on the product development model of banana rope woven baskets. The survey respondents chose style 1 with pleats on top like wrapping a dumpling in order to put the filling inside and wrap the dumpling's mouth tightly so that it wouldn't come out. It is comparable to the storage temperature of food. The frame of the basket weave pattern is dyed red and purple banana rope, contrasting with the cream color of the undyed banana rope. And from the survey of consumer satisfaction towards the development of banana rope woven basket products in terms of containers, usage aspects. and average overall satisfaction of 4.71, 5.00 and 4.87.